MEDIA PEMBELAJARAN PUZZLE DALAM MENINGKATKAN KEMAMPUAN BERBICARA BAHASA ARAB DI MADRASAH IBTIDAIYAH (MI) - Lailatul Maghfiroh (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
This study aims to analyze the effectiveness of using puzzle media in improving students’ Arabic speaking skills (maharah al-kalam) in Madrasah Ibtidaiyah (Islamic Elementary Schools). The method used is a literature review, involving the analysis of books, academic journals, and previous studies related to Arabic language learning media. The findings indicate that puzzle media positively influence students’ motivation, participation, and comprehension in the learning process. As an interactive medium, puzzles create an enjoyable and collaborative learning environment while enhancing students’ vocabulary, pronunciation, and sentence structure in Arabic. Moreover, the implementation of puzzle media aligns with constructivist and communicative learning theories that emphasize active student involvement in constructing knowledge. Therefore, puzzle media can be considered an innovative and effective teaching strategy to enhance Arabic speaking skills at the elementary level.